2018
DOI: 10.2472/jsms.67.811
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Open Fracture’s Multifarious Effects on Ultrasonic Wave Propagation in Rock Masses

Abstract: A comprehensive understanding of the fracture's effects on wave propagation is a necessary prerequisite for estimating the dynamic behavior of fractured rock masses. This study presents a series of ultrasonic experiments on the multifarious effects of open fractures on the propagation characteristics of waves, considering various geometric parameters of fractures. The results indicate that fractures disrupt the waveform and attenuates the wave amplitude and velocity. With the increase of fracture width, the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…For LSP‐1 and LSP‐3, the magnitude of ε NE AT is nonuniform for the three UIA regions, where the greatest reduction in the transmitted signal amplitude corresponds to the highest strain values (UIA‐3 for LSP‐1 and UIA‐1 and UIA‐2 for LSP‐3 in Figure b). These observations further corroborate the findings of Kurtuluş et al (), Modiriasari et al (, ), and Yang et al () that the presence of cracks caused by locally tensile strain concentrations is the primary cause of attenuation in the ultrasonic wave amplitude in intact rock. Furthermore, these results suggest that the selected strain metrics provide a practically useful representation of microcrack damage in rock for the purposes of understanding ultrasonic wave attenuation.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For LSP‐1 and LSP‐3, the magnitude of ε NE AT is nonuniform for the three UIA regions, where the greatest reduction in the transmitted signal amplitude corresponds to the highest strain values (UIA‐3 for LSP‐1 and UIA‐1 and UIA‐2 for LSP‐3 in Figure b). These observations further corroborate the findings of Kurtuluş et al (), Modiriasari et al (, ), and Yang et al () that the presence of cracks caused by locally tensile strain concentrations is the primary cause of attenuation in the ultrasonic wave amplitude in intact rock. Furthermore, these results suggest that the selected strain metrics provide a practically useful representation of microcrack damage in rock for the purposes of understanding ultrasonic wave attenuation.…”
Section: Resultssupporting
confidence: 91%
“…Cai and Zhao (2000) also noted that high-frequency waves (ultrasonic waves) propagating through a fractured material are attenuated (and slowed), with each of the fractures contributing individually to wave attenuation like a single discrete feature. Similarly, Huang et al (2014) and Yang et al (2018) found that fractures lead to the loss in transmission (reduction in amplitude) of the high-frequency ultrasonic waves. Based on its definition, any increase in the magnitude of the ε NE AT is analogous to the formation, accumulation, and growth of extensile microcracks in the rock specimens.…”
Section: 1029/2018jb017086mentioning
confidence: 90%
See 2 more Smart Citations
“…The presence of such a large number of bioactive ions, and particularly the high magnesium content, makes eggshell an excellent precursor for the synthesis of the bioactive hydroxyapatite. Various methods of the hydroxyapatite synthesis have been developed, including: dry methods (solid-state synthesis and the mechanochemical process), wet methods (conventional chemical precipitation, hydrolysis method, hydrothermal method, emulsion method, sol-gel method and sonochemical method), hightemperature processes (combustion method and pyrolysis process), microwave processing, synthesis from biogenic sources, as well as combination procedures [1][2][3][4][5][6][9][10][11]. The chemical precipitation method has been the most popular one, since it's versatile and has certain economic advantages [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%